Die Börse: Moral der Gewinner?: die ethische Problematik von Börsengeschäften - Malatiésta, Claus (Zeitschrift für katholische Theologie, 2001)
Although the market instrument "share" is defined by a more technical understanding of the exchange mechanism and therefore at least at the first glance "share" has very little to do with morality, the behaviour of the one who uses this instrument is governed by moral criteria. This explains, why the losses that one makes through shares form the real moral problem and not the gains. The neutrality of the market should not obscure the fact that its justification lies on a more general and pretentious level than that of money. From this perspective the centre place of the share changes. In the last instance, money does not stay at the centre, although, still, value is transformed into money, but man who is answerable about his responsibility. With a basically oriented perspective come into play thought processes and value systems, which make the transaction of share an indicator of the society. In this sense, share is more than a mathematically determinable connection between offer and demand, it shows tendencies of the society from which the levels of moral sensitivity can be recognized.